Exploring the Influence of Clinical Externships on Newly Graduated Nurses’ Transition to Practice - Hembrey, Jessi; Hallaran, Amy; Woodend, Kirsten (Quality Advancement in Nursing Education / Avancées en formation infirmière, 2025)
Purpose: In 2021, the Ontario government began funding clinical externships to help hospitals faced with significant human health resource issues during the COVID-19 pandemic. Clinical externships provide students an opportunity to work alongside nurses as unregulated health care workers in hospitals. Limited research is available related to clinical externship programs in Ontario, with most research focusing on programs in the United States, measuring retention, and studying how students felt during or immediately after the completion of the programs. The aim of this study was to explore how newly graduated nurses (NGNs) felt their participation in a clinical externship program influenced their transition from student to nurse.Methods: This study used interpretive description as its research methodology. Exploring associations, relationships, and patterns within a phenomenon while borrowing elements from the more traditional qualitative techniques, interpretive description was chosen to generate an understanding of participant experiences that would be relevant and useful to clinical practice. Using social media and purposive sampling, nurses in their first year of practice who worked as a clinical extern while in nursing school were recruited to participate. Eight NGNs completed interviews. Interviews were transcribed verbatim, and data analysis used a constant comparative approach.Results: Three main themes emerged: developing self-efficacy, developing a professional identity, and being on the inside. Clinical externships gave participants exposure to the clinical setting over and above those offered by clinical placements and consolidations in the nursing program. This exposure provided participants the opportunity to develop self-efficacy in skills, assessments, and communication; start to develop a sense of themselves as nursing professionals; and gain an insider glimpse into the realities of nursing.Conclusion: This study contributes to the knowledge of how clinical externships may influence the transition to practice of NGNs in Ontario and has several implications for various relevant groups. Nursing educators must advocate for adequate clinical exposure and hands-on experiences, integrating more experiential learning opportunities into nursing curriculum. Researchers, policy makers, and practice leaders must also collaborate to evaluate externship programs to help inform continued programs and opportunities for improvement.